Contributions to a List of First Reviser actions: ornithology - David, Normand; Dickinson, Edward; Gregory, Steven (Zootaxa, 2009)
A record of First Reviser actions is needed and ZooBank is apparently expected to collect these. In support of this we provide some contributions both to assist with the creation of the appropriate data fields within ZooBank and to stimulate greater awareness of the retroactivity of Art. 24.2.4 of the International Code of Zoological Nomenclature. Of 66 cases collected relating to ornithology, and solely to dual or multiple original spellings, 45 are cases where, in consequence of this Article, under the Principle of Priority, an earlier nomenclatural act requires recognition in replacement of more recent acts. In just a few cases the consequence is a spelling that has not been in recent use. We also act as First Revisers in 10 additional cases discovered during our research.